Concepções e práticas de psicólogos(as) escolares e docentes acerca das adaptações curriculares : um estudo em contextos públicos de educação - Gomes, Wanessa de Macêdo (2023)
The global movement for inclusion has become a political, cultural, social and pedagogical issue. As a result, the organization of schools must be rethought, implying structural and cultural change so that everyone has their specificities met. A relevant part of the discussion and effectiveness of inclusion in an educational context are curricular adaptations, which constitute an important tool for reflection and proposition of a responsive teaching to those who demand access to the offered educational proposal. The psychologist is considered an important professional to act as a mediator in the interrelation between the Specialized Educational Service (AEE), the multifunctional resource room and the elaboration of the development plan individual and school given that it can collaborate to enable the child's access to the school's curricular proposals. Given the above, the objective of this study is to understand and analyze the conceptions and practices of school psychologists and teachers about curricular adaptations in public schools in the city of João Pessoa-PB. As part of the study, the theme of inclusion was explored and discussed, with emphasis on curricular adaptations as a tool to make it effective, and a literature survey was carried out in order to investigate, in national and international databases, whether and how psychologists have acted facing demands for curricular adaptations. This investigation ratified, in the researched form, that there is a shortage of scientific productions in the field of psychology in dialogue with curricular adaptations. A qualitative field research was carried out in elementary schools in the municipal public network of João Pessoa-PB. The study included 10 school psychologists, 10 teachers from Elementary School I, and 10 teachers from Specialized Educational Assistance (AEE), who answered a sociodemographic questionnaire and a semi-structured interview. The analysis of the sociodemographic questionnaire showed that eight psychologists participated in specific training to work in the school area, seven took an improvement course related to inclusive education; nine AEE teachers and six teachers from the regular classroom took training focused on school inclusion, and nine AEE teachers and five from the regular classroom took further training related to inclusive education. These data indicate that professionals have sought to deepen their knowledge about the question investigated and improve their practices aimed at inclusive education. The analysis of the interviews was guided by the general guidelines of Bardin (1977) and organized into general axes for analysis. The results showed, through the speeches of the school psychologists, that there are joint actions carried out more frequently with the teachers of the AEE and of the regular classroom for the elaboration of the curricular adaptations, according to the Axes of Analysis: 'Participating in the Planning' and 'Guiding teachers '. However, it is important to reflect on how school psychologists have been working with teachers and how psychological work can specifically contribute to making curricular adaptations. With regard to the understanding of curriculum adaptation, the psychologists' responses indicate that they conceive it as: 'Adapting activities according to the degree of mentality/intelligence level', 'Individualized for each student' and 'Meeting the student's needs'. The teachers, on the other hand, presented in their speeches conceptions about curricular adaptations that refer to 'Making the activity/content accessible', 'Equivalent to the PEI [Individualized Teaching Plan]' and 'Achieving an objective/target of the content'. It is noticed that the professors express notions that converge with each other and that are close to the concepts found in the literature on curricular adaptations. However, it is worth noting that the PEI is an instrument that enables the implementation of curriculum adaptations. This study reaffirms the importance of school psychologists in teaching institutions, as mediators in the interrelationship between AEE and regular classroom teachers. For the implementation of these actions, it is essential to carry out continuous in-service training for Education professionals on the process of school inclusion of students with disabilities and/or special educational needs, and a deepening of theoretical-methodological procedures that favor teaching-learning processes that respect the different rhythms and styles of learning that characterize the human psyche. In this way, the school psychologist can contribute with knowledge about human development, learning processes, defend in their praxis the accessibility and equity of programmatic curricular contents, and collaborate with an inclusive education.